Management of Planning, Organizing, and Implementation of Arabic Language Learning - Lutfi, Muhammad Fuad Khasan; Aminudin; Ngantori; Sisran (Journal of Educational Management Research, 2025)
This study aims to examine the implementation of Arabic language learning management at the Al-Jauharen course institution, highlighting its advantages and potential as a model for other institutions seeking to improve Arabic language education quality. The study employs a descriptive qualitative field research approach, focusing on the Al-Jauharen course institution. Data collection methods include observations at the institution, interviews with the head and teachers, and document review. Data analysis follows the Miles and Huberman model, which involves data collection, reduction, presentation, and conclusion drawing. The findings reveal that the Arabic language learning program planning at the Al-Jauharen institution begins with determining the program, preparing learning materials, selecting media, and choosing appropriate methods and approaches. Organizationally, the program involves task division, lesson scheduling, evaluation and improvement planning, student activity scheduling, and provision of necessary facilities. The implementation process consists of three stages: introduction, core activities, and closing. These structured steps contribute to the effective learning management at the institution.